Economic determinants of breastfeeding in Haiti: The effects of poverty, food insecurity, and employment on exclusive breastfeeding in an urban population. Issue 2 (4th October 2017) - Lesorogol, Carolyn; Bond, Caitlin; Dulience, Sherlie Jean Louis; Iannotti, Lora
Abstract: There is limited and inconsistent empirical evidence regarding the role of economic factors in breastfeeding practices, globally. Studies have found both negative and positive associations between low income and exclusive breastfeeding (EBF). Employment, which should improve household income, may reduce EBF due to separation of mother and infant. In the context of a randomized controlled study of lipid‐based complementary feeding in an urban slum in Cap Haitien, Haiti, we examined the economic factors influencing breastfeeding practices using mixed methods. Findings demonstrate relationships between urban context, economic factors, and breastfeeding practices. Poverty, food insecurity, time constraints, and limited social support create challenges for EBF. Maternal employment is associated with lower rates of EBF and less frequent breastfeeding. Extreme food insecurity sometimes leads to increased exclusive breastfeeding among Haitian mothers, what we call "last resort EBF." In this case, women practice EBF because they have no alternative food source for the infant. Suggested policies and programs to address economic constraints and promote EBF in this population include maternal and child allowances, quality child care options, and small‐scale household urban food production.